Penggunaan Media Video Animasi Berbasis Geosapasial dalam Meningkatkan Kemampuan Berpikir Kritis terhadap Mitigasi Bencana Tsunami - Hidiyah, Tabita May; Sumarmi, Sumarmi; Bachri, Syamsul; Mkumbachi, Ramadhani Lausi (J-PIPS (Jurnal Pendidikan Ilmu Pengetahuan Sosial), 2023)
Low critical thinking skills and lack of utilization of learning media are still high in Indonesia, so research was conducted to see the effect of utilizing geospatial-based animated video learning media on critical thinking skills. This research used quasy experiment method with Pretest-Postest control group design. The research subjects were 65 students of XI social studies class at SMAN Pesanggaran Banyuwangi Regency consisting of XI social studies class 1 as the experimental class with 35 students and XI social studies class 3 as the control class with 30 students. Determination of research subjects using purposive sampling technique.   Data collection using tests in the form of essay questions as an instrument of critical thinking skills. Independent Sample t-test conducted with SPSS 26.0 For Windows became the hypothesis test of this study. The results showed that the media had a positive effect with sig. 0,003 0,05. In conclusion, geospatial-based animated video media can improve students' critical thinking skills on tsunami disaster mitigation sub-materials.